2019
DOI: 10.2174/1871520618666180801101730
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of A Novel GLP-1R Ligand for PET Imaging of Prostate Cancer

Abstract: Glucagon-like peptide 1 receptor (GLP-1R) is an important biomarker for diagnosis and therapy of the endocrine cancers due to overexpression. Recently, in human prostate cancer cell lines the receptor was also observed, therefore it may be a potential target for the disease. 18F-Al-NOTA-MAL-Cys39-exendin-4 holds great promise for GLP-1R. Therefore, the feasibility of the 18F-labeled exendin-4 analog for prostate cancer imaging was investigated; 2) Methods: New probe 18F-Al-NOTA-MAL-Cys39-exendin-4 was made thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This labeling process took only 30 min and the final product did not require further purification. We then validated the characteristics of 18 F-Al-NOTA-MAL-Cys 39 -exendin-4 such as high specificity and low abdominal uptake, and demonstrated its reliable diagnostic performance in diabetes, insulinoma and prostate cancer [21][22][23]. In this present study, we intend to develop another novel radiotracer using positron nuclide 68 Ga.…”
mentioning
confidence: 75%
“…This labeling process took only 30 min and the final product did not require further purification. We then validated the characteristics of 18 F-Al-NOTA-MAL-Cys 39 -exendin-4 such as high specificity and low abdominal uptake, and demonstrated its reliable diagnostic performance in diabetes, insulinoma and prostate cancer [21][22][23]. In this present study, we intend to develop another novel radiotracer using positron nuclide 68 Ga.…”
mentioning
confidence: 75%
“…GLP1R (Glucagon Like Peptide 1 Receptor) is a Protein Coding gene which is a member of G protein coupled receptor family. GLP-1R is an important target when treating of type 2 diabetes and obesity [32][33][34]. Recent studies have shown that GLP-1R activation has a cytoreductive effect on human pancreatic cancer cells [35].…”
Section: Discussionmentioning
confidence: 99%